2011
DOI: 10.4236/jep.2011.25061
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Paints Causes Impairment of Kidney Functions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…An occupational disease is any chronic ailment that occurs as a result of work or occupational activity. It is an aspect of occupational safety and health, typically identified when the disease is more prevalent in a given group of workers compared with the general population or with other groups of workers [1] [2]. The assessment of occupational diseases therefore provides models for understanding environmental diseases.…”
Section: Introductionmentioning
confidence: 99%
“…An occupational disease is any chronic ailment that occurs as a result of work or occupational activity. It is an aspect of occupational safety and health, typically identified when the disease is more prevalent in a given group of workers compared with the general population or with other groups of workers [1] [2]. The assessment of occupational diseases therefore provides models for understanding environmental diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with renal impairments may have increased oxidant activity and a reduced antioxidant capacity, and this is increased in a graded manner with increasing renal dysfunction [25]. A study on painters who had worked for more than ten years supported the hypothesized association between solvent exposure and the development of chronic renal failure [26]. However, another study of a small group of male metal degreasers in Sweden observed no increase in NAG excretion into the urine, concluding that TCE was not nephrotoxic at low exposure levels [27].…”
Section: Discussionmentioning
confidence: 97%
“…These substances have been shown to have demonstrable nephrotoxic, 4 hepatotoxic 5 and hematotoxic 6 effects similar to the results of the present study. Accordingly, Al-Ghamdi, 7 studied the kidney function of car painters who had prolonged exposure to paint fumes and found a significant higher mean serum value of Cr, Ur and UA than levels in the unexposed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive metabolites from paints and other solvents can also cause physiochemical damage to the glomerular membrane and tubules due to their high lipophilicity. 7 Such damage has been shown to alter the functional integrity of the membrane, impairs Na + /K + /ATPase activity and several other enzymes involved in ionic and acid-base balance. Also, associated tubular damage can cause tubular dysfunction, impairs renal excretory function, macula densa cell signaling mechanisms, renal hemo-dynamics/autoregulation and poor handling of metabolic waste products with a resultant increase in serum Cr, Ur and UA as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%